The role of gender in small scale irrigation agriculture among smallholder farmers in Lume District in the Central Rift Valley of Ethiopia - Fikirie, K. (Wondo Genet College of Forestry and Natural Resources, 2016)
Ethiopian economy predominantly depends on rain-fed agriculture. The sector is anticipated to support the whole economy and to change its structure. However, the country is highly affected by drought and millions of people are left without sustenance frequently. As an option, small scale irrigation schemes are important to reduce vulnerability and increase productivity. In this aspect, it is important to consider the implication of gender in irrigation crop farming under small scale scheme. This study therefore investigated irrigation agriculture among small-holder farmers and the role of gender in Lume district in the Central Rift Valley of Ethiopia. Both quantitative and qualitative data collection was used and purposive sampling technique was used to select four PAs in the district that dominantly practice irrigation agriculture out of a total 13 PAs. Households were stratified into male headed (MHH) and female headed (FHH) and simple random sampling was used to proportionally select 165 households from both groups (135 MHH and 30 FHH). Key informant interview, focus group discussions and household survey were used to collect primary data. The data analysis was carried out by using descriptive statistics, one way ANOVA and chi-square tests. Results of the study showed that there was a significant difference in irrigation crop preference between male and female headed households. Male headed households mostly prefer high value crops such as onion, tomato and cabbage, while FHH prefer easily manageable and low water demanding crops. Results on engagement in management practices revealed that FHH mainly participate in planting, weeding, hoeing, harvesting, while MHH are widely involved in land clearing, cultivation, crop watering, disease and pest control and transporting. With regard to cash income generation from small scale irrigation, the study revealed that MHH are mainly involved in seed production particularly the high value onion seeds while FHH are widely participate in selling of seedlings. However, there was no significant difference between MHH and FHH in involvement in cash income generating activities. On the other hand, the result also indicates that MHH have got better training, access to extension service and access to improved seeds than FHH. In addition, both MHH and FHH encountered market problem for different irrigation crops. Furthermore, there was no significant difference between MHH and FHH in fertilizer and chemical application. The study has concluded that gender has significant roles and implications in small scale irrigation agriculture through its direct influence in participation, labor division, crop preference and involvement in income generating activities. Therefore, the study suggests that improving the involvement of female headed households in irrigation agriculture special consideration should be given by government and non-governmental organization.